PENERAPAN TATA KELOLA PERUSAHAAN YANG BAIK (GOOD CORPORATE GOVERNANCE) DALAM PELAKSANAAN TANGGUNG JAWAB SOSIAL (CORPORATE SOCIAL RESPONSIBILITY) PADA PT. PERTAMINA EP RANTAU KABUPATEN ACEH TAMIANG - Simon Simon; Bismar Nasution; Sunarmi Sunarmi; Mahmul Siregar (Universitas Sumatera Utara, 2018)
ABSTRACT Implementation of corporate social responsibility by using good governance is done by one of the companies in Indonesia, namely PT. PERTAMINA EP RANTAU Kabupaten Aceh Tamiang. PT. PERTAMINA EP RANTAU Aceh Tamiang District manages business with ethical behavior with regard to people, profit and planet. The location of good corporate governance in the implementation of corporate social responsibility is reflected in the synergy of corporate social responsibility activities that involve the active role of the community and local government in accordance with existing resources and the principles of local wisdom through Social Mapping and Focus Group Discussion in areas that belong to the region work, namely Aceh Tamiang and Langkat districts. Keywords: Corporate Social Responsibility, Good Corporate Governance, and Company